2019
DOI: 10.5194/isprs-archives-xlii-2-w15-1023-2019
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Automatic 3d Parametrization of Non-Planar Surfaces From Point Clouds in Hbim Applications

Abstract: 3D laser scanning and photogrammetric 3D reconstruction generate point clouds from which the geometry of BIM models can be created. However, a few methods do this automatically for concrete architectural elements, but in no case for the entirety of heritage assets. A novel procedure for the automatic recognition and parametrization of non-planar surfaces of heritage immovable assets is presented using point clouds as raw input data. The methodology is able to detect the most relevant architectural features in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Model creation-Arguably the next evolution of point cloud segmentation is where a modelling algorithm detects areas of the point cloud belonging to a single object, separates the point and then creates a 3D object in that place. This method has been investigated and applied with some success to individual work [96], but there is yet to be a fully automated process [97]. Other works have repeatedly concluded that modelling algorithms are not yet developed enough to model complex architecture or differences due to aging [73,74,[98][99][100].…”
Section: Increasing Modelling Speed and Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Model creation-Arguably the next evolution of point cloud segmentation is where a modelling algorithm detects areas of the point cloud belonging to a single object, separates the point and then creates a 3D object in that place. This method has been investigated and applied with some success to individual work [96], but there is yet to be a fully automated process [97]. Other works have repeatedly concluded that modelling algorithms are not yet developed enough to model complex architecture or differences due to aging [73,74,[98][99][100].…”
Section: Increasing Modelling Speed and Qualitymentioning
confidence: 99%
“…[45] suggests that modelling requires a degree of technical insight regarding constructive techniques which cannot be automatically determined. The most successful automatic modelling techniques model geometric primitives [97,101]. Of these, the accuracy is potentially insufficient for certain use cases, with [97] only achieving a distance accuracy for columns of approximately 64 mm.…”
Section: Increasing Modelling Speed and Qualitymentioning
confidence: 99%
See 1 more Smart Citation